Children’s Learning from Touch Screens: A Dual Representation Perspective - Sheehan, Kelly J.; Uttal, David H. (Frontiers in Psychology, 2016)
Parents and educators often expect that children will learn from touch screen devices, such as during joint e-book reading. Therefore an essential question is whether young children understand that the touch screen can be a symbolic medium – that entities represented on the touch screen can refer to entities in the real world. Research on symbolic development suggests that symbolic understanding requires that children develop dual representational abilities, meaning children need to appreciate that a symbol is an object in itself (i.e., picture of a dog) while also being a representation of something else (i.e., the real dog). Drawing on classic research on symbols and new research on children’s learning from touch screens, we offer the perspective that children’s ability to learn from the touch screen as a symbolic medium depends on the effect of interactivity on children’s developing dual representational abilities. Although previous research on dual representation suggests the interactive nature of the touch screen might make it difficult for young children to use as a symbolic medium, the unique interactive affordances may help alleviate this difficulty. More research needs to investigate how the interactivity of the touch screen affects children’s ability to connect the symbols on the screen to the real world. Given the interactive nature of the touch screen, researchers and educators should consider both the affordances of the touch screen as well as young children’s cognitive abilities when assessing whether young children can learn from it as a symbolic medium.